Chemical synthesis of nitric oxide in the stomach from dietary nitrate in humans. (February 1997) - McKnight, G M; Smith, L M; Drummond, R S; Duncan, C W; Golden, M; Benjamin, N
Abstract : BACKGROUND/AIMS: It has been suggested that dietary nitrate, after concentration in the saliva and reduction to nitrite by tongue surface bacteria, is chemically reduced to nitric oxide (NO) in the acidic conditions of the stomach. This study aimed to quantify this in humans. METHODS: Ten healthy fasting volunteers were studied twice, after oral administration of 2 mmol of potassium nitrate or potassium chloride. Plasma, salivary and gastric nitrate, salivary and gastric nitrite, and gastric headspace NO concentrations were measured over six hours. RESULTS: On the control day the parameters measured varied little from basal values. Gastric nitrate concentration was 105.3 (13) mumol/l (mean (SEM), plasma nitrate concentration was 17.9 (2.4) mumol/l, salivary nitrate concentration 92.6 (31.6) mumol/l, and nitrite concentration 53.9 (22.8) mumol/l. Gastric nitrite concentrations were minimal (< 1 mumol/l). Gastric headspace gas NO concentration was 16.4 (5.8) parts per million (ppm). After nitrate ingestion, gastric nitrate peaked at 20 minutes at 3430 (832) mumol/l, plasma nitrate at 134 (7.2) mumol/l, salivary nitrate at 1516.7 (280.5) mumol/l, and salivary nitrite at 761.5 (187.7) mumol/l after 20-40 minutes. Gastric nitrite concentrations tended to be low, variable, and any rise was non-sustained. Gastric NO concentrations rose considerably from 14.8 (3.1) ppm to 89.4 (28.6) ppm (p < 0.0001) after 60 minutes. All parameters remained increased significantly for the duration of the study. CONCLUSIONS: A very large and sustained increase in chemically derived gastric NO concentrations after an oral nitrate load was shown, which may be important both in host defence against swallowed pathogens and in gastric physiology.